Global change effects on biogeochemical processes of Argentinian estuaries: an overview of vulnerabilities and ecohydrological adaptive outlooks - Kopprio, Germán Adolfo (2015)
The aims of this work are to provide an overview of the current stresses of estuaries in Argentina and to propose adaptation strategies from an ecohydrological approach. Several Argentinian estuaries are impacted by pollutants, derived mainly from sewage discharge and agricultural or industrial activities. Anthropogenic impacts are expected to rise with increasing human population. Climate-driven warmer temperature and hydrological changes will alter stratification, residence time, oxygen content, salinity, pollutant distribution, organism physiology and ecology, and nutrient dynamics. Good water quality is essential in enhancing estuarine ecological resilience to disturbances brought on by global change. The preservation, restoration, and creation of wetlands will help to protect the coast from erosion, increase sediment accretion rates, and improve water quality by removing excess nutrients and pollutants. The capacity of hydrologic basin ecosystems to absorb human and natural impacts can be improved through holistic management, which should consider social vulnerability in complex human–natural systems.